Relationship of Expression of HER2/neu with other Prognostic Factors in Invasive Breast Cancers (Journal of Fatima Jinnah Medical University, 2018)
Background: Breast Carcinoma (CA Breast) is the commonest malignancy in females other than skin and is second to lung cancer as a cause of cancer deaths worldwide. The treatment of CA Breast has dramatically changed after the advent of molecular classification of CA Breast. The hormone receptors status and HER2/neu expression in CA Breast are weak prognostic but powerful predictive factors for CA Breast. HER2/neu expression in CA Breast patients generally imparts a poor prognosis and decreased survival to the disease. The objective of this study was to correlate the expression of HER2/neu with other prognostic factors in invasive carcinoma of breast.Patients and Methods: We carried out a comparative cross sectional study in the Pathology department of Fatima Jinnah Medical University, Lahore from January 2015 to August 2017. A total of 163 cases of biopsy proven CA Breast, which had been reported as HER2/neu 3+ on immunohistochemistry (IHC), were reviewed. Data including age of the patient, size of the tumor, histological type of tumor, grade of tumor, and status of the regional lymph nodes were retrieved from the Pathology department. SPSS version 17 was used for analysis of the data.Results: Out of the 163 cases, 83 cases were modified radical mastectomy specimens (MRM), while 80 cases were Tru-Cut specimens, incisional biopsies and wedge biopsies. Only 1 patient in this study was male, rests were females. Age ranged from 23 to 80 years, 87.7 % patients were ≥ 35 years. Invasive carcinoma of no special type (NST) was seen in 158, 2 cases were invasive lobular carcinoma, and 3 cases were mucinous carcinoma. The tumors were graded using the Bloom Richardson grading system. None was grade I, 138 cases (84.7%) showed histological grade II, rest 25 cases (18.3%) had grade III morphology. Amongst the MRM cases, only 9 cases (11%) showed tumor size ≤ 2cm, 74 cases (89%) showed tumor size > 2cm. Out of the 83 MRM cases, 64 cases (77%) showed regional lymph node metastasis.Conclusion: Our results showed that HER2/neu expression in CA Breast patients is related with increasing age, more often with invasive carcinoma (NST) as compared to other histological types, bigger tumor size, higher histological grade and presence of lymph nodes metastasis.
Keywords: HER2/neu, cancer breast, prognostic factors